Discrimination and Depressive Symptoms Among Latina/o Adolescents of Immigrant Parents. (January 2016) - Lopez, William D.; LeBrón, Alana M. W.; Graham, Louis F.; Grogan-Kaylor, Andrew
Discrimination is associated with negative mental health outcomes for Latina/o adolescents. While Latino/a adolescents experience discrimination from a number of sources and across contexts, little research considers how the source of discrimination and the context in which it occurs affect mental health outcomes among Latina/o children of immigrants. We examined the association between source-specific discrimination, racial or ethnic background of the source, and school ethnic context with depressive symptoms for Latina/o adolescents of immigrant parents. Using multilevel linear regression with time-varying covariates, we regressed depressive symptoms on source-specific discrimination, racial or ethnic background of the source of discrimination, and school percent Latina/o. Discrimination from teachers (β = 0.06, p  < .05), students (β = 0.05, p  < .05), Cubans (β = 0.19, p  < .001), and Latinas/os (β = 0.19, p  < .001) were positively associated with depressive symptoms. These associations were not moderated by school percent Latina/o. The findings indicate a need to reduce discrimination to improve Latina/o adolescents' mental health.